Design of Resource Management System Continuing Education - Rezeki, Ketiara; Mildansyah, Mildansyah; Kalsum, Ummi; Pulungan, Lilik Hidayat (Lembaga Riset Mutiara Akbar, 2024)
Education is very important in life because it is closely related to the formation of national character so it must remain sustainable. So it becomes important to design a sustainable education resource management system. There are several steps taken in improving the quality of education and managing educational resources comprehensively. These include coaching and development, increasing the motivation of educational resources, supervision and monitoring, and allocating an education budget. In the process of sustainable education resource management, coaching and professional development of teachers is very important, because it will also have an impact on the quality of schools/madrasas, but it should be noted that efforts to foster and develop the competence of educators should be followed by the participation of the government, both central and local governments, this must also be supported by stakeholders such as communities that support the development of educational institutions